Needles of cure a bibliography of acupuncture titles in the medical and Chinese libraries, University of Singapore - Cheng, Michael (Bibliographical series - University of Singapore Library, 1976)
Some 390 entries to books and journal articles, as well as list of journals cited. Except for 135 books cited in Chinese, all references are in English. Subject index to journal articles.